Artificial Intelligence for Learning Independence Among Indonesian Senior High School Students - Akhir Winardi; Utami Dewi Indriyati; Maya Intan Restiyadi Putri; Rilla Sovitriani (Advanced Journal of STEM Education, 2025)
This literature review aims to examine the utilization of artificial intelligence (AI) in supporting self-directed learning for students aged 17 to 18 years. The advancement of Artificial intelligence technology offers significant potential in transforming the learning process, particularly in providing more personalized, adaptive, and interactive learning experiences.  Through a literature review method of 13 relevant journals and school research published between 2020 and 2025, this study analyzes various implementations of artificial intelligence in the context of self-directed learning. The analysis results indicate that artificial intelligence can function as personal virtual tutors, adaptive learning systems, learning chatbots, game-based learning platforms, artificial intelligence-based assessment systems, educational data analysis tools, and automatic evaluation systems.  The utilization of artificial intelligence has proven effective in enhancing students skills, abilities, and intelligence, as well as providing support to educators in the learning process.  Nevertheless, this study also emphasizes that the role of educators remains crucial, and artificial intelligence is not intended to replace the function of educators in educating and shaping students character.  Active supervision and guidance from parents and educators are necessary to ensure the wise and effective utilization of artificial intelligence in self-directed learning.